How should the world respond to natural disasters? - O'Connor, Rebecca (Farmington Hills, MI Greenhaven Press, 2006)
A collection of seventeen controversial essays that debate issues relating to natural disasters including international response to disasters, who should provide aid, and whether or not the government discriminates against the poor in natural disasters.
The international response to natural disasters must be improved / Ed Tsui -- International donors save many lives / UNICEF -- International efforts to limit the devastation of natural disasters are inadequate / Emma Young -- An Indian Ocean tsunami warning system must be developed / Costas Synolakis -- Creating an Indian Ocean tsunami warning system is futile / Keith Alverson -- Developing countries lack adequate disaster prevention and recovery programs / Suprakash Roy -- Developed nations must help poorer countries modernize / Ross Clark -- Trauma counseling helps disaster victims / Sherwin B. Nuland -- Trauma counseling may not help victims / Erzulie Coquillon -- The U.S. government's response to disasters discriminates against the poor and minorities / Ted Steinberg -- Nations should provide aid for humanitarian reasons alone / The Economist -- Developers should build more carefully on coastlines / David M. Bush, William J. Neal, Robert S. Young -- People should not live in hazard-prone areas / Seth R. Reice -- Relief agencies must dispel myths about natural disasters / Claude de Ville de Goyet -- Relief agencies should study past disasters / Thomas R. DeGregori -- Hurricane Katrina revealed the weakness of U.S. emergency response / Paul Light -- A belief in God can protect against disasters / John Ross Schroeder.
Includes bibliographical references (p. 127-134) and index.
Keywords: Natural disaster warning systems; Disaster relief; Emergency management